PENGARUH PENGGUNAAN CERUCUK TERHADAP KUAT GESER TANAH LEMPUNG LUNAK - Soewignjo Agus Nugroho; Arie S Sibarani (Jurnal APTEK, 2013)
Clay soil is a soil type which has a low bearing capacity so that it will face problems if the clay is receiving considerable expense. One alternative to improve the bearing capacity of clay soil is to provide a ditusukan cerucuk into it. This study aimed to discover how much influence cerucuk use of soft clay soil strength.The method used is by the addition of wood with a diameter pole cerucuk ± 8 cm in the soft clay which then will be tested with a shear tester (Vane Shear Test) with the length and spacing cerucuk cerucuk varied.The results after cerucuk anchored into the clay soil showed an increase in shear strength of clay soil, compared with a shear strength values without cerucuk. For 60 cm long with a space cerucuk 2D, 3D, 5D, respectively 5.25%, 2.20%, 1.06%. For 80 cm long with a space cerucuk 2D, 3D, 5D, respectively for 25.15%, 20.73%, 18.91%. For cerucuk 100 cm long with a spacing of 2D, 3D, 5D, respectively for 33.80%, 31.63%, 29.93%. With this we can conclude that the longer the cerucuk and the closer the distance between cerucuk, the more can increase the shear strength of clay soil.